Preparation method of ultrahigh-heat-conductivity silicon nitride ceramic chip

Through the combination technology of ball milling and casting molding, laminated glue discharge, and modified polysilazane binder, the problem of low thermal conductivity of silicon nitride ceramics is solved, and the preparation of ultra-high thermal conductivity of silicon nitride ceramics is realized. Its thermal conductivity and bending strength are improved.

CN119191853AActive Publication Date: 2024-12-27江苏富乐华功率半导体研究院有限公司

Patent Information

Application Number
CN202411376302.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The current silicon nitride ceramics have low thermal conductivity, and high-temperature sintering and long-term insulation cannot continuously improve thermal conductivity, so other ways need to be explored to improve their thermal conductivity.

Method used

The slurry is made by ball milling and casting, and the glue is laminated through boron nitride powder to control the amount of magnesium oxide and the β-Si3N4 seeds, and combined with modified polysilazane as a binder to protect the atmosphere. Sintering, optimize the sintering parameters to improve the thermal conductivity of the silicon nitride ceramic sheet.

Benefits of technology

It significantly improves the thermal conductivity and bending strength of silicon nitride ceramic sheets, avoids the generation of miscellaneous phases during high-temperature sintering, and meets the practical application requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191853A_ABST
    Figure CN119191853A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an ultrahigh-heat-conductivity silicon nitride ceramic chip, and relates to the technical field of silicon nitride ceramic chips. Comprising the following steps: step 1, carrying out ball milling and defoaming on raw materials to prepare slurry, and carrying out tape casting to obtain a green body; step 2, laminating the green bodies with the boron nitride powder therebetween for glue discharging to obtain laminated green bodies; and step 3, sintering the laminated green body in a protective atmosphere to obtain the ultrahigh-heat-conduction silicon nitride ceramic chip. The preparation method has the beneficial effects that the addition amount of magnesium oxide is controlled, and the seed crystal is added, so that the growth of crystal grains is controlled while the addition of additional oxygen content is reduced, and the heat conductivity and bending strength of the obtained silicon nitride ceramic chip are improved. And meanwhile, the binder is partially introduced into the modified polysilazane, so that the quality of the silicon nitride ceramic chip is improved, the generation of impure phases in the high-temperature sintering process is avoided, and the practical application is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicon nitride ceramic sheets, and in particular to a method for preparing an ultra-high thermal conductivity silicon nitride ceramic sheet. Background Art

[0002] With the rapid development of my country's high-speed rail, aerospace, military industry and other fields, the demand for high-power power electronic devices will increase in the future. In order to adapt to more complex and harsh application conditions, high-power power electronic devices are developing towards high temperature, high frequency, low power consumption, intelligence, modularization and systematization, which poses a severe challenge to the heat dissipation of the entire electronic device. The function of the substrate in the power device is to absorb the heat generated by the chip and transfer it to the heat sink to achieve heat exchange with the outside world. Therefore, the preparation of high thermal conductivity substrate materials has become the key to the research and development of high-power module electronic products. However, the actual thermal conductivity of silicon nitride ceramics is still far lower than the theoretical thermal conductivity value, and some high thermal conductivity silicon nitride ceramics are still in the laboratory stage.

[0003] At present, the factors that affect the thermal conductivity of silicon nitride ceramics include lattice oxygen, crystal phase, grain boundary phase, etc. Among them, the increase in silicon nitride grain size is conducive to improving thermal conductivity, but when the grain size reaches a critical value, the increase in grain size has no obvious effect on improving the thermal conductivity of silicon nitride. Therefore, it is no longer possible to continuously improve thermal conductivity by only promoting abnormal growth of silicon nitride grains through high-temperature sintering and long-term heat preservation, and other more effective ways must be explored. The lattice oxygen content in silicon nitride will reduce the thermal conductivity of silicon nitride. Part of the oxygen content in the lattice oxygen comes from oxide-based sintering aids. The addition of magnesium oxide is to promote the densification and grain growth of silicon nitride and provide an environment for grain growth, but too much will affect the thermal conductivity of silicon nitride. The current main method is to replace oxide additives with non-oxide additives, but it is still in the research and development stage and cannot be mass-produced.

[0004] Therefore, in order to solve the above problems, a method for preparing an ultra-high thermal conductivity silicon nitride ceramic sheet is prepared. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing an ultra-high thermal conductivity silicon nitride ceramic sheet to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing an ultra-high thermal conductivity silicon nitride ceramic sheet comprises the following steps:

[0008] Step 1: ball milling and degassing the raw materials to make slurry and tape casting to obtain green body;

[0009] Step 2: stacking the green body with boron nitride powder to remove binder, so as to obtain a laminated green body;

[0010] Step 3: Under a protective atmosphere, the laminated green body is sintered to obtain an ultra-high thermal conductivity silicon nitride ceramic sheet.

[0011] More optimally: the raw materials of the ultra-high thermal conductivity silicon nitride ceramic tile include the following components: by weight, 60-75 parts of silicon powder, 30-75 parts of solvent, 0.25-2.5 parts of dispersant, 3-30 parts of binder, 10-30 parts of plasticizer, 1.5-8 parts of yttrium oxide, 1.5-6 parts of magnesium oxide, and 1-3 parts of β-Si3N4 seed crystals.

[0012] More optimally: the debinding parameters are set as follows: heating to 500-900°C at a heating rate of 2-5°C / min, and keeping warm for 4-24h;

[0013] The sintering parameters are set as follows: gas pressure of 0.1-10 MPa, heating to 1650° C.-1900° C. at a heating rate of 1-5° C. / min, and heat preservation for 18-48 hours.

[0014] More optimally: the dispersant includes one or more of castor oil, fish oil, and glyceride; the plasticizer includes one or more of dioctyl phthalate and dibutyl phthalate; and the solvent includes one or two of isopropanol and ethyl acetate.

[0015] In a further embodiment, the solvent is isopropanol and ethyl acetate in a mass ratio of 1:(1-2.5).

[0016] More optimally: the binder is polyvinyl butyral.

[0017] More optimally, the binder is polyvinyl butyral and modified polysilazane in a mass ratio of 2-2.2:1-1.8.

[0018] More optimally: the preparation process of the modified polysilazane is:

[0019] S1: Under a protective atmosphere, vinyl polysilazane is dissolved in xylene, thiosalicylic acid and azobisisobutyronitrile are added and mixed, the mixture is heated to 50-60°C, and the reaction is carried out for 3-4 hours to obtain intermediate A;

[0020] S2: Mix the intermediate A, melamine, 1,3-dicyclohexylcarbodiimide, N-hydroxysuccinimide and ethylene glycol, raise the temperature to 70-80° C., and react for 4-5 hours to obtain modified polysilazane.

[0021] More optimally, the intermediate A comprises the following components: by weight, 20-30 parts of vinyl polysilazane, 100-120 parts of xylene, 15-20 parts of thiosalicylic acid, and 1-2 parts of azobisisobutyronitrile; the modified polysilazane comprises the following components: by weight, 10-12 parts of intermediate A, 5-8 parts of melamine, 0.5-1 part of 1,3-dicyclohexylcarbodiimide, 0.5-1 part of N-hydroxysuccinimide, and 60-80 parts of ethylene glycol.

[0022] More optimally: With the increase of Si3N4 grain size, the distribution of intergranular phase will change, and the number of intergranular phase thin layers between two adjacent grains will decrease. Within a certain size range, the increase of grains can increase the thermal conductivity of Si3N4. The growth of grains can be controlled by adjusting the amount of magnesium oxide added. However, too much magnesium oxide will increase the lattice oxygen content in silicon nitride, thereby affecting the thermal conductivity of silicon nitride.

[0023] Therefore, the present invention controls the amount of magnesium oxide added and matches the addition of seed crystals, thereby reducing the addition of additional oxygen content and controlling the growth of grains, thereby improving the thermal conductivity of the obtained silicon nitride ceramic tile. At the same time, silicon nitride ceramic tiles are easily oxidized during high-temperature sintering, and the oxidized substances will penetrate into the surface of the ceramic tile, forming a new impurity phase at high temperature, affecting the thermal conductivity. Therefore, the present invention introduces modified polysilazane into the binder part. On the one hand, the modified polysilazane is mixed with silicon nitride powder, which helps to form a casting slurry with a certain colloidal viscosity, and can be spread into a uniform film on the film tape during the casting process to form a ceramic tile with uniform thickness; on the other hand, the modified polysilazane can decompose reducing gas under high temperature conditions to prevent the formation of impurity phases. The details are as follows:

[0024] (1) Adding an appropriate amount of large-sized β-Si3N4 seeds to the Si3N4 raw material can promote the rapid dissolution and precipitation of fine particles on the β-Si3N4 seeds during sintering, increase the driving force for grain growth, and promote the growth of β-Si3N4 grains. The growth of grains is conducive to the gradual expulsion of the grain boundary phase into the polycrystalline junction, reducing the distribution of the grain boundary phase in the lattice, thereby improving thermal conductivity;

[0025] (2) Vinyl polysilazane is subjected to a click reaction to obtain intermediate A, and then melamine groups are grafted through an amidation reaction to obtain modified polysilazane. In the preparation process of silicon nitride ceramic sheets, modified polysilazane and polyvinyl butyral act as binders together, and the two work synergistically to effectively improve the quality of silicon nitride ceramic sheets. At the same time, the melamine groups grafted by the modified polysilazane can act as a reducing agent to generate reducing gases under high temperature conditions, thereby avoiding the generation of impurities during high-temperature sintering and reducing thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a SEM image of the silicon nitride ceramic sheet obtained in Example 1 of the present invention;

[0027] Figure 2 This is a SEM image of the silicon nitride ceramic sheet obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] It should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions and are exemplified as follows: in the following embodiments, vinyl polysilazane CAS is 503590-70-3, and the brand is Lana White; 1,3-dicyclohexylcarbodiimide CAS is 538-75-0, and the manufacturer is Qianyan Chemical Technology (Wuhan) Co., Ltd.; N-hydroxysuccinimide CAS is 6066-82-6, and the manufacturer is Shanghai MacLean Biochemical Technology Co., Ltd.

[0030] Embodiment 1: This embodiment provides an ultra-high thermal conductivity silicon nitride ceramic sheet, and the specific preparation method is as follows:

[0031] Step 1: 65 parts of silicon powder, 65 parts of solvent isopropanol / ethyl acetate (the mass ratio of the two is 1:1), 1.5 parts of glycerol, 20 parts of polyvinyl butyral, 20 parts of dioctyl phthalate, 3.5 parts of yttrium oxide, 2.5 parts of magnesium oxide and 2 parts of β-Si3N4 seed crystals are ball-milled and degassed to make a slurry, and then tape-casted to obtain a green body;

[0032] Step 2: In a nitrogen atmosphere, the green body is stacked with boron nitride powder at a heating rate of 2°C / min to 500°C, and the temperature is kept for 4 hours to perform binder removal to obtain a laminated green body;

[0033] Step 3: Sinter the laminated green body in a nitrogen atmosphere, raise the temperature to 1850°C at a heating rate of 5°C / min at a pressure of 10 MPa, and keep it for 45 hours to obtain an ultra-high thermal conductivity silicon nitride ceramic sheet.

[0034] Embodiment 2: This embodiment provides an ultra-high thermal conductivity silicon nitride ceramic sheet, and the specific preparation method is as follows:

[0035] Step 1: 65 parts of silicon powder, 65 parts of solvent isopropanol / ethyl acetate (the mass ratio of the two is 1:2.5), 1.5 parts of glycerol, 20 parts of polyvinyl butyral, 10 parts of modified polysilazane, 20 parts of dioctyl phthalate, 5 parts of yttrium oxide, 3 parts of magnesium oxide and 2 parts of β-Si3N4 seed crystals are ball-milled, degassed to make a slurry and tape-cast to obtain a green body;

[0036] Step 2: In a nitrogen atmosphere, the green body is stacked with boron nitride powder at a heating rate of 5°C / min to 900°C, and the temperature is kept for 24 hours to perform binder removal to obtain a laminated green body;

[0037] Step 3: Sintering the laminated green body in a nitrogen atmosphere, heating the temperature to 1850°C at a rate of 5°C / min at a pressure of 10 MPa, and keeping the temperature for 45 hours to obtain an ultra-high thermal conductivity silicon nitride ceramic sheet;

[0038] Wherein, the preparation process of modified polysilazane is:

[0039] S1: Under a protective atmosphere, 30 parts of vinyl polysilazane were dissolved in 100 parts of xylene, 15 parts of thiosalicylic acid and 1 part of azobisisobutyronitrile were added and mixed, the temperature was raised to 60°C, and the reaction was carried out for 3 hours to obtain intermediate A;

[0040] S2: 10 parts of intermediate A, 6 parts of melamine, 0.5 parts of 1,3-dicyclohexylcarbodiimide, 0.5 parts of N-hydroxysuccinimide and 80 parts of ethylene glycol were mixed, the temperature was raised to 80° C., and the reaction was performed for 5 hours to obtain modified polysilazane.

[0041] Embodiment 3: This embodiment provides an ultra-high thermal conductivity silicon nitride ceramic sheet, and the specific preparation method is as follows:

[0042] Step 1: 70 parts of silicon powder, 75 parts of solvent isopropanol / ethyl acetate (the mass ratio of the two is 1:1), 1.5 parts of glycerol ester, 20 parts of polyvinyl butyral, 10 parts of modified polysilazane, 20 parts of dioctyl phthalate, 6 parts of yttrium oxide, 5 parts of magnesium oxide and 2 parts of β-Si3N4 seed crystals are ball-milled and degassed to prepare slurry and tape-cast to obtain a green body;

[0043] Step 2: In a nitrogen atmosphere, the green body is stacked with boron nitride powder at a heating rate of 2°C / min to 600°C, and the temperature is kept for 24 hours to perform binder removal to obtain a laminated green body;

[0044] Step 3: Sintering the laminated green body in a nitrogen atmosphere, heating the temperature to 1850°C at a rate of 5°C / min at a pressure of 10 MPa, and keeping the temperature for 45 hours to obtain an ultra-high thermal conductivity silicon nitride ceramic sheet;

[0045] Wherein, the preparation process of modified polysilazane is:

[0046] S1: Under a protective atmosphere, 30 parts of vinyl polysilazane were dissolved in 100 parts of xylene, 15 parts of thiosalicylic acid and 1 part of azobisisobutyronitrile were added and mixed, the temperature was raised to 60°C, and the reaction was carried out for 3 hours to obtain intermediate A;

[0047] S2: 10 parts of intermediate A, 6 parts of melamine, 0.5 parts of 1,3-dicyclohexylcarbodiimide, 0.5 parts of N-hydroxysuccinimide and 80 parts of ethylene glycol were mixed, the temperature was raised to 80° C., and the reaction was performed for 5 hours to obtain modified polysilazane.

[0048] Comparative Example 1: Adding an excess of β-Si3N4 seed crystals, the rest is the same as Example 1, specifically as follows:

[0049] Step 1: 65 parts of silicon powder, 65 parts of solvent isopropanol / ethyl acetate (the mass ratio of the two is 1:1), 1.5 parts of glycerol, 20 parts of polyvinyl butyral, 20 parts of dioctyl phthalate, 3.5 parts of yttrium oxide, 2.5 parts of magnesium oxide and 4 parts of β-Si3N4 seed crystals are ball-milled and degassed to make a slurry, and then tape-casted to obtain a green body;

[0050] Step 2: In a nitrogen atmosphere, the green body is stacked with boron nitride powder at a heating rate of 5°C / min to 900°C, and the temperature is kept for 24 hours to perform binder removal to obtain a laminated green body;

[0051] Step 3: Sinter the laminated green body in a nitrogen atmosphere, raise the temperature to 1850°C at a heating rate of 5°C / min at a pressure of 10 MPa, and keep the temperature for 45 hours.

[0052] Comparative Example 2: No β-Si3N4 seed crystals were added, and the rest was the same as Example 1, specifically as follows:

[0053] Step 1: 65 parts of silicon powder, 65 parts of solvent isopropanol / ethyl acetate (the mass ratio of the two is 1:1), 1.5 parts of glycerol, 20 parts of polyvinyl butyral, 20 parts of dioctyl phthalate, 3.5 parts of yttrium oxide, and 2.5 parts of magnesium oxide are ball-milled and degassed to prepare a slurry, and then tape-casted to obtain a green body;

[0054] Step 2: In a nitrogen atmosphere, the green body is stacked with boron nitride powder at a heating rate of 5°C / min to 900°C, and the temperature is kept for 24 hours to perform binder removal to obtain a laminated green body;

[0055] Step 3: Sinter the laminated green body in a nitrogen atmosphere, raise the temperature to 1850°C at a heating rate of 5°C / min at a pressure of 10 MPa, and keep the temperature for 45 hours.

[0056] Comparative Example 3: Excessive magnesium oxide was added, and the rest was the same as in Example 1, specifically as follows:

[0057] Step 1: 65 parts of silicon powder, 65 parts of solvent isopropanol / ethyl acetate (the mass ratio of the two is 1:1), 1.5 parts of glycerol, 20 parts of polyvinyl butyral, 20 parts of dioctyl phthalate, 3.5 parts of yttrium oxide, 8 parts of magnesium oxide and 2 parts of β-Si3N4 seed crystals are ball-milled and degassed to make a slurry, and then tape-casted to obtain a green body;

[0058] Step 2: In a nitrogen atmosphere, the green body is stacked with boron nitride powder at a heating rate of 5°C / min to 900°C, and the temperature is kept for 24 hours to perform binder removal to obtain a laminated green body;

[0059] Step 3: Sinter the laminated green body in a nitrogen atmosphere, raise the temperature to 1850°C at a heating rate of 5°C / min at a pressure of 10 MPa, and keep the temperature for 45 hours.

[0060] Comparative Example 4: No magnesium oxide was added, and the rest was the same as Example 1, specifically as follows:

[0061] Step 1: 65 parts of silicon powder, 65 parts of solvent isopropanol / ethyl acetate (the mass ratio of the two is 1:1), 1.5 parts of glycerol, 20 parts of polyvinyl butyral, 20 parts of dioctyl phthalate, 3.5 parts of yttrium oxide and 2 parts of β-Si3N4 seed crystals are ball-milled and degassed to make a slurry, and then tape-casted to obtain a green body;

[0062] Step 2: In a nitrogen atmosphere, the green body is stacked with boron nitride powder at a heating rate of 5°C / min to 900°C, and the temperature is kept for 24 hours to perform binder removal to obtain a laminated green body;

[0063] Step 3: Sinter the laminated green body in a nitrogen atmosphere, raise the temperature to 1850°C at a heating rate of 5°C / min at a pressure of 10 MPa, and keep the temperature for 45 hours.

[0064] Detection experiment:

[0065] (1) The silicon nitride ceramic sheets obtained in Example 1 and Comparative Examples 1-5 were tested for three-point bending strength using a universal testing machine, with a span of 30 mm and a pressing speed of 0.5 mm / min. The critical load when the sample broke was determined and the bending strength was calculated as follows:

[0066]

[0067] Among them, F represents the breaking load, that is, the maximum force that the material can withstand in the bending test; L represents the span, that is, the distance between the support points; b represents the width of the specimen; d represents the thickness of the specimen.

[0068] (2) The silicon nitride ceramic sheets obtained in Example 1 and Comparative Examples 1-5 were subjected to laser flash spectroscopy to measure the thermal diffusion coefficient and calculate the thermal conductivity in the following manner:

[0069] λ=ρ×Cp×α

[0070] Among them, λ is thermal conductivity; α is thermal diffusion coefficient; ρ is density; Cp is specific heat capacity.

[0071] The obtained data are shown in the following table:

[0072]

[0073] Table 1

[0074] Conclusion: Example 2-3 controls the amount of magnesium oxide added and adds seed crystals, reduces the amount of additional oxygen added, controls the growth of grains, and improves the thermal conductivity and bending strength of the silicon nitride ceramic sheet. At the same time, the modified polysilazane is introduced into the binder part, which improves the quality of the silicon nitride ceramic sheet and avoids the generation of impurities during high-temperature sintering, which is in line with practical applications.

[0075] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an ultra-high thermal conductivity silicon nitride ceramic sheet, characterized in that: The following steps are involved: Step 1: ball milling and degassing the raw materials to make slurry and tape casting to obtain green body; Step 2: stacking the green body with boron nitride powder to remove binder, so as to obtain a laminated green body; Step 3: Under a protective atmosphere, the laminated green body is sintered to obtain an ultra-high thermal conductivity silicon nitride ceramic sheet.

2. The method for preparing an ultra-high thermal conductivity silicon nitride ceramic sheet according to claim 1, characterized in that: The raw materials of the ultra-high thermal conductivity silicon nitride ceramic sheet include the following components: by weight, 60-75 parts of silicon powder, 30-75 parts of solvent, 0.25-2.5 parts of dispersant, 3-30 parts of binder, 10-30 parts of plasticizer, 1.5-8 parts of yttrium oxide, 1.5-6 parts of magnesium oxide, and 1-3 parts of β-Si3N4 seed crystals.

3. The method for preparing an ultra-high thermal conductivity silicon nitride ceramic sheet according to claim 1, characterized in that: The debinding parameters are set as follows: heating to 500-900°C at a heating rate of 2-5°C / min and keeping warm for 4-24h; The sintering parameters are set as follows: the gas pressure is 0.1-10 MPa, the temperature is increased to 1650° C.-1900° C. at a heating rate of 1-5° C. / min, and the temperature is kept for 18-48 hours.

4. The method for preparing an ultra-high thermal conductivity silicon nitride ceramic sheet according to claim 2, characterized in that: The dispersant includes one or more of castor oil, fish oil, and glyceride; the plasticizer includes one or more of dioctyl phthalate and dibutyl phthalate; and the solvent includes one or two of isopropanol and ethyl acetate.

5. The method for preparing an ultra-high thermal conductivity silicon nitride ceramic sheet according to claim 2, characterized in that: The binder is polyvinyl butyral.

6. The method for preparing an ultra-high thermal conductivity silicon nitride ceramic sheet according to claim 2, characterized in that: The binder is polyvinyl butyral and modified polysilazane in a mass ratio of 2-2.2:0.8-1.

7. The method for preparing an ultra-high thermal conductivity silicon nitride ceramic sheet according to claim 6, characterized in that: The preparation process of the modified polysilazane is: S1: Under a protective atmosphere, vinyl polysilazane is dissolved in xylene, thiosalicylic acid and azobisisobutyronitrile are added and mixed, the mixture is heated to 50-60°C, and the reaction is carried out for 3-4 hours to obtain intermediate A; S2: Mix the intermediate A, melamine, 1,3-dicyclohexylcarbodiimide, N-hydroxysuccinimide and ethylene glycol, raise the temperature to 70-80° C., and react for 4-5 hours to obtain modified polysilazane.

8. The method for preparing an ultra-high thermal conductivity silicon nitride ceramic sheet according to claim 7, characterized in that: The intermediate A comprises the following components: by weight, 20-30 parts of vinyl polysilazane, 100-120 parts of xylene, 15-20 parts of thiosalicylic acid, and 1-2 parts of azobisisobutyronitrile; the modified polysilazane comprises the following components: by weight, 10-12 parts of intermediate A, 5-8 parts of melamine, 0.5-1 part of 1,3-dicyclohexylcarbodiimide, 0.5-1 part of N-hydroxysuccinimide, and 60-80 parts of ethylene glycol.

Citation Information

Patent Citations

  • Batch sintering method of high-performance silicon nitride ceramic substrate

    CN112811912A

  • High-thermal-conductivity silicon nitride ceramic and preparation method thereof

    CN113480318A

  • Silicon wafer tape casting slurry and silicon wafer forming method

    CN115611639A

  • Silicon nitride ceramic sintering aid, high-thermal-conductivity silicon nitride ceramic and preparation method of high-thermal-conductivity silicon nitride ceramic

    CN117303917A

  • Silicon nitride ceramic substrate and preparation method thereof

    CN118359442A

Cited By

  • Electronic ceramic slurry and preparation method thereof

    CN119930302A

  • Silicon nitride ceramic chip and surface treatment process thereof

    CN119930326A

  • Preparation method of reactive sintering silicon nitride ceramic chip

    CN120923248A

  • A method for preparing a reaction-sintered silicon nitride wafer

    CN120923248B

  • Pulping method of multi-particle-size silicon powder slurry

    CN120965347A